The Effectiveness of a Wireless Modular Bed Absence Sensor Device for Fall Prevention among Older Inpatients - Subermaniam, Kogilavani; Welfred, Ridgwan; Subramanian, Pathmawathi; Chinna, Karuthan; Ibrahim, Fatimah; Mohktar, Mas S.; Tan, Maw Pin (Frontiers in Public Health, 2017)
Background Falls and fall-related injuries are increasingly serious issues among elderly in-patients due to population ageing. The bed exit alarm has only previously been evaluated in a handful of studies with mixed results. We therefore evaluated the effectiveness of a modular bed absence sensor device (M-BAS) in detecting bed exits among older in-patients in a middle income nation in East Asia. Methods Patients aged ≥65 years on an acute geriatric ward who were able to mobilize with or without walking-aids and physical assistance were recruited to the study. The total number of alarms, and the numbers of true and false alarms were recorded by ward nurses. The M-BAS device is placed across the mattress of all consenting participants. Nurses’ workload was assessed using the National Aeronautics and Space Administration-Task Load Index (NASA-TLX) score while nurses’ perceptions were surveyed. Results The sensitivity of the M-BAS was 100% with a positive predictive value of 68% and a nuisance alarm rate of 31%. There was a significant reduction in total NASA-TLX workload score (mean difference = 14.34 ± 13.96 SD, p<0.001) at the end of the intervention period. 83% of the nurses found the device useful for falls prevention, 97% found it user friendly and 87% would use it in future. Conclusion The M-BAS was able to accurately detect bed absence episodes among geriatric in-patients and alert nurses accordingly. The use of the device significantly reduced the total workload score, while the acceptability of the device was high among our nurses. A larger, cluster randomized study to measure actual falls outcome associated with the use of the device is now indicated.